Analysis of Syirkah practices in cattle farming within Islamic economics in Tanjung Jabung Timur - Fidiyani; Wargo; Kuswanto (Zabags Qu Publish, 2025)
This study is motivated by the imperative to advance Islamic economics in Indonesia through the application of the syirkah partnership contract in agribusiness, which holds strong potential to improve rural welfare. Tanjung Jabung Timur was selected as the research locus due to its significant cattle-farming capacity, where cooperation practices remain largely traditional and informal, and often fall short of formal Sharia requirements. The study aims to identify prevailing forms of cooperation in cattle farming, assess their alignment with the syirkah framework in Islamic economics, and delineate implementation challenges. Employing a qualitative phenomenological approach, data were collected through observation, in-depth interviews, and documentation, then analyzed using thematic analysis and triangulation. Findings indicate that syirkah practices commonly rely on trust and oral agreements, which contribute to household income yet face constraints in capital, market access, and legal-Sharia literacy. The article contributes theoretically by extending discourse on syirkah within agribusiness, and practically by proposing a more equitable, transparent, and actionable cooperation model that can inform local and national Islamic economic policy. It also underscores the need to integrate classical jurisprudential principles with contemporary institutional design to enhance sustainability and compliance.